3D silicon shapes through bulk nano structuration by focused ion beam implantation and wet etching. (25th April 2017) - Salhi, Billel; Troadec, David; Boukherroub, Rabah
Abstract: The work presented in this paper concerns the synthesis of silicon (Si) 2D and 3D nanostructures using the delayed effect, caused by implanted Ga ions, on the dissolution of Si in aqueous solutions of tetramethylammonium hydroxide (TMAH). The crystalline silicon substrates (100) are first cleaned and then hydrogenated by immersion in an aqueous solution of hydrofluoric acid. The ion implantation is then carried out by a focused ion beam by varying the dose and the exposure time. Chemical etching in aqueous solutions of TMAH at 80 °C leads to the selective dissolution of the Si planes not exposed to the ions. The preliminary results obtained in the laboratory made it possible to optimize the experimental conditions for the synthesis of 2D and 3D nanoobjects of controlled shape and size. Analysis by transmission electron microscopy and energy dispersive x-ray showed the amorphous nature of the nanostructures obtained and the presence of 5%–20% Ga in these nanoobjects. The first experiments of recrystallization by rapid thermal annealing allowed to reconstitute the crystal structure of these nanoobjects.